Engineering management the foundations of technical leadership - Wardin, Kate (O'Reilly Media, Inc., 2023)
If you recently transitioned from an engineering role to a people manager, you may be struggling with the psychological shift that comes with pivoting your focus from computer science to people science. But even if you've managed the move so far with ease, or are already a seasoned technical leader, continuing to practice a few key techniques can ensure you feel more prepared and confident leading your technical team. This self paced course walks you through fundamental techniques that will help you navigate the complexities of engineering management. What you'll learn and how you can apply it How to give effective and actionable feedback Tactical techniques to manage your time effectively Tips and tricks for building an effective developer onboarding experience Ways to empower your team members to ensure they reach (and surpass) their full potential Facilitate straightforward, productive, and enjoyable one-on-ones Identify key focus areas to be an effective engineering manager and leader for your team's unique needs Establish a motivating team vision to help propel your team through the toughest challenges Strategies for fostering diverse and inclusive teams This course is for you because... You're an individual contributor interested to learn about the expectations of an Engineering Manager You're looking to move into an Engineering Manager role in the near future You're an existing Engineering Manager, Tech Lead, etc and want to explore the fundamentals of the role Materials or downloads needed in advance: A handout will be provided for download that will be referenced throughout the course.
Online resource; title from title details screen (O'Reilly, viewed April 23, 2024)
Keywords: Engineering -- Personnel management; Engineering personnel; Engineering -- Management; Ingénierie; Personnel; Direction; Personnel en ingénierie; Ingénierie; Gestion; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet